Deconstructing the liability of foreignness: Regulatory enforcement actions against foreign banks - Wu, Zheying; Salomon, Robert (Journal of International Business Studies, 2017)
It is widely acknowledged that foreign firms are at an institutional disadvantage relative to domestic firms operating in the local market. This “liability of foreignness” typically manifests as inferior performance for foreign firms relative to domestic competitors. Although myriad studies document the liability of foreignness, few demonstrate how individual host country institutions generate specific liabilities. In this study, we explore the regulatory liabilities that foreign firms face using a sample of 189 foreign banks operating in the United States. We find that regulators initiate more enforcement actions, on average, against foreign banks than they do against domestic banks. The effects, however, vary by regulation type and firm characteristics. For example, foreign banks are no more likely to receive risk-related sanctions, but far more likely to receive stakeholder-related sanctions. Foreign banks with higher quality of human capital and more host country experience are less likely to run afoul of all regulations. Foreign banks with more third country experience are less likely to receive risk-related sanctions, but more likely to receive stakeholder-related sanctions. The results highlight the contingent nature of regulatory liabilities, the role of information asymmetry versus regulatory bias in enforcement outcomes, and the liability-reducing effects of resources and capabilities.